Magnetic and thermolectric properties of topological graphene heterostructures - Almeida, Patrícia de Assis (2022)
In this dissertation, we will present a study of the electronic, magnetic, transport and thermoelectric properties of recently synthesized one-dimensional heterostructures that are built upon a `backbone' constituted by an armchair graphene nanoribbon (AGNR). Such heterostructures have been successfully synthesized, in gold surfaces, through chemical processes. The interest in these heterostructures has greatly increased after it was predicted that they should have topologically non-trivial bands near the Fermi energy. This theoretical prediction has been experimentally confirmed in the last couple of years. Their topological properties stem from localized states (themselves topological in nature) that may appear at the different junctions forming the heterostructure. The hybridization of those states simulates, close to the Fermi energy, a Su-Schrieffer-Heeger model (i.e., a dimerized chain), endowing the low-energy physics of the system with topological properties. Here, we do not study their topological properties. Rather, using the Landauer formalism, we first analyze their thermoelectric properties, viz., charge and electronic thermal conductances, as well as the Seebeck coefficient, denoted as $G$, $K_e$, and $S$, respectively. This allows us to calculate the linear-response thermocurrent $\nicefrac{I_{th}}{Δ T}=GS$, as well as the figure of merit $ZT=\nicefrac{GS^2T}{K_e}$ ($T$ stands for temperature), which estimates the efficiency of a material in transforming thermal into electrical energy. Our results indicate that some of the (semiconducting) heterostructures analyzed have a considerably larger figure of merit than that of the AGNR backbone upon which they are built. Next, using the tight-binding formalism, we show that these heterostructures present a multitude of flat-bands, reminiscent of the single flat-band already studied in pristine AGNRs. These flat-bands occur due to the formation of so-called `Wannier orbital states', through a quantum interference process. After carefully analyzing their electronic properties using a tight-binding model, we were able to show, for the first time, through a collaboration with a DFT in-house group, that hole-doping these heterostructures leads to a ferromagnetic ground state. A future research direction in this subject could be the study of the interplay between ferromagnetism and topology in some of these interesting systems.